Social Vulnerability and How It Matters: A Bibliometric Analysis - Toharudin, Toni; Suprijadi, Jadi; Caraka, Rezzy Eko; Pontoh, Resa Septiani; Chen, Rung Ching; Lee, Youngjo; Pardamean, Bens (International Journal of Criminology and Sociology, 2021)
Interdisciplinary and cross-cultural studies of the impacts of environment and social vulnerability must be undertaken to address the problem of social vulnerability in the foreseeable future. Scientist or social scientists should first continuously strive towards approaches can integrate municipal technological expertise, experiences, knowledge, perceptions, and expectations into emergency circumstances, so that people can be sharper on issues and offer responses with their matters. In this paper. We performing the Bibliometric Analysis to review published papers on the keyword ’Social Vulnerability’. There are 29,468 papers published in the last 52 years from 1969 to November 2020. Disaster research by implementing the Internet of Things (IoT), data mining, machine learning is still needed.